Efficacy and safety of short duration azithromycin eye drops versus azithromycin single oral dose for the treatment of trachoma in children: a randomised, controlled, double-masked clinical trial. Issue 5 (27th September 2006) - Cochereau, Isabelle; Goldschmidt, Pablo; Goepogui, André; Afghani, Tayyab; Delval, Laurent; Pouliquen, Pascale; Bourcier, Tristan; Robert, Pierre-Yves
Abstract : Aims: Efficacy and safety of a short-duration treatment of azithromycin 1.5% eye drops versus oral azithromycin to treat active trachoma. Methods: Randomised, controlled, double-masked, double-dummy, non-inferiority explanatory study including 670 children from Guinea Conakry and Pakistan if: 1–10 years old; active trachoma (TF+TI0 or TF+TI+ on simplified World Health Organisation (WHO) scale). Three groups received either: azithromycin 1.5% eye drops twice daily for 2 days, for 3 days or azithromycin single 20 mg/kg oral dose. Patients' contacts were treated whenever possible. Clinical evaluation was performed using a binocular loupe. Primary efficacy variable was the cure (no active trachoma (TF0)) at day 60. Non-inferiority margin for difference between cure rates was 10%. Results: Cure rate in per protocol set was as follows: 93.0%, 96.3% and 96.6% in 2-day group 3-day group, and oral treatment group, respectively. Azithromycin 1.5% groups were non-inferior to oral azithromycin. The intend to treat (ITT) analysis supported the results. Clinical re-emergence rate was low: 4.2%. Ocular tolerance was similar for all groups. No treatment related adverse events were reported. Logistic regression analyses found prognostic factors such as: country (p<0.001) and trachoma severity (p = 0.003). Conclusions: In active trachoma, azithromycin eye drops twice daily for 2 or 3 days are as efficient as the WHO's reference treatment and represent an innovative alternative to oral azithromycin.